The Implementation and Review of Cognitive Remediation Training for First Episode Psychosis in Singapore - Chong, Nigel Ian Ming; Maniam, Yogeswary; Chua, Yi Chian; Tang, Charmaine (Frontiers in Psychiatry, 2021)
Objective Early intervention in patients with first episode psychosis (FEP) can improve cognitive abilities, with both short- and long-term benefits. In this paper, we describe the implementation and review of cognitive remediation training (CRT) in an Asian FEP population. The outcomes of the training are also evaluated and discussed. Methods This naturalistic paper describes in detail the real-life implementation and conduct of CRT in an early psychosis intervention service. 109 patients with FEP underwent a 24-session CRT programme, using Cogpack and Neuropsychological Educational Approach to Remediation. The program is evaluated with pre- and post-CRT assessment scores which included Montreal Cognitive Assessment and Brief Assessment of Cognition in Schizophrenia. The rates of improvement on these cognitive assessments were evaluated using paired t-tests, with statistical significance set at p ≤ 0.05. Results Of the 109 patients who underwent CRT, a total of 92 (84.4%) completed all 24 sessions. Paired t-tests between pre- and post-CRT assessments scores revealed that participants significantly improved on majority of the measures, including verbal memory, digit sequencing, and symbol coding. Conclusion As with other cognitive remediation programmes, CRT has shown to improve cognitive functioning in patients with FEP. The results support the use of CRT in an Asian context and may serve as guidance for the implementation of similar training programmes in other Asian early psychosis intervention services.